DETERMINING FACTORS OF PURCHASE INTENTION AND WILLINGNESS TO PAY PROCESS - Maylandi, Putri; Kurniawati, Kurniawati (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This inquire about was conducted to Analyze the Determinants of Eagerness to Pay (WTP) by understanding what drives consumers' greatest cost resistance. This is a associative type of quantitative approach. The time horizon is cross-sectional. The unit of analysis is individual who are Muslim fashion consumers. Survey conducted by distribute the questionnaire in December 2023 using Google Forms to 361 sample. Seven variables were tested, consisting of 33 questions on a five-point Likert scale. Structural Equation Modeling (SEM) is used to examine data. The findings of a test of the hypothesis that Purchase Intention is significantly positively impacted by Brand Personality, Social Influence, and Brand Reputation. Purchase intention significantly improves eWOM and decision-making. Willingness to Pay is significantly improved by decision-making and eWOM. Brand Personality, Social Influence, and Brand Reputation are factors to attract interest in buying Muslim fashion products. Keywords: Purchase Intention; Willingness to Pay; Decision-making; eWOM; Muslim Fashion